2013
DOI: 10.1590/s0104-64972013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the cladoceran Bosmina huaronensis Delachaux, 1918 and niche differentiation among populations from different biogeographic regions

Abstract: -Described from a high-altitude lake in Peru, Bosmina huaronensis Delachaux, 1918 has been recorded in diverse kinds of water bodies in South and North America, suggesting that this species has high environmental tolerance and a wide niche breadth. The present study surveyed the occurrence records of B. huaronensis from 55 localities and, using multivariate analysis, investigated the niche differentiation among populations from different biogeographic regions, based on altitude and seven climatic variables. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The species of this family are common widespread planktonic filter feeders (e.g. Melo and Hebert, 1994;Elmoor-Loureiro, 2013) and registers for the studied reservoir has already been provided (Panarelli et al, 2008(Panarelli et al, , 2010Sartori et al, 2009). This habitat architecture is the optimal habitat for planktonic taxa, thus the increased and exclusive number of planktonic species.…”
Section: Discussionmentioning
confidence: 93%
“…The species of this family are common widespread planktonic filter feeders (e.g. Melo and Hebert, 1994;Elmoor-Loureiro, 2013) and registers for the studied reservoir has already been provided (Panarelli et al, 2008(Panarelli et al, , 2010Sartori et al, 2009). This habitat architecture is the optimal habitat for planktonic taxa, thus the increased and exclusive number of planktonic species.…”
Section: Discussionmentioning
confidence: 93%
“…The morphology of appendages and other structures was studied using an Olympus phase-contrast microscope BX41 attached to a camera lucida. All individuals were identified with the support of taxonomic specialized references (Smirnov, 1996;Elmoor-Loureiro, 1997;Kotov and Štifter, 2006;Sinev and Elmoor-Loureiro, 2010;Sinev, 2004;Van Damme et al, 2011;Van Damme and Sinev, 2013). The voucher specimens were preserved in ethanol and deposited in the personal collection of FDRS (accession numbers FDRS486-495).…”
Section: Sampling Sorting and Identificationmentioning
confidence: 99%
“…Next, Elmoor-Loureiro (2013) reported Bosmina huaronensis; Sousa et al, (2015a) indicated the occurrence of Coronatella paulinae Sousa, ElmoorLoureiro & Santos, 2015(as C. poppei (Richard, 1897) and Flavalona margipluma (Sousa, Santos, Güntzel, Diniz, Melo-Júnior & Elmoor-Loureiro, 2015) (= Alona margipluma Sousa, Santos, Güntzel, Diniz, Melo-Júnior & Elmoor-Loureiro, 2015in Sousa et al, 2015b. Nevertheless, a higher number of species than are currently known in Lake Paranoá is presumed to exist, because its geographical position is within the distribution range of at least 37 species (Sousa and Elmoor-Loureiro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to some freshwater animals with a great decline (if not a collapse) of taxonomic studies, Cladocera (Crustacea: Branchiopoda) is an example of a model group with a relatively "healthy" taxonomy. Several tropical countries are intensively studying it now, such as Mexico [14,15], Brazil [16][17][18], Columbia [19][20][21] or Ecuador [22]. Unfortunately, faunistic studies have almost stopped in many western countries or are conducted by some non-professional enthusiasts [23].…”
Section: Introductionmentioning
confidence: 99%